Between International Integration and National Autonomy in Favour of Concrete Cases: The Italian Constitutional Court’s ‘Internationally Oriented Automatism’s Prohibition’ Doctrine - Perona, Riccardo (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2019)
This paper deals with a peculiar doctrine of the Italian Constitutional Court, the “prohibition of legislative automatisms,” which is used, in some judgments, in an internationally oriented form. My argument is that this doctrine can be seen as an effective legal and constitutional instrument operating in the “multi-level” scenario and namely in the framework of international systems and treaties of human rights protection. Indeed, it provides a good degree of flexibility and a good balancing point between international integration and national autonomy in light of the need to reach an adequate and “fair” solution in the concrete case and, therefore, in favour of the enhancement of human rights protection at the practical level.